Direct Yaw-moment Control with a F-TDMA Scheduler for Electric Vehicle. Issue 1 (February 2021) - Cao, Wanke; Liu, Jizhi; He, Yong
Abstract: This paper proposed a new scheduling approach for direct yaw-moment control (DYC) of distributed-driven electric vehicles (EVs) over a controller area network (CAN). The insertion of the communication network makes the system a distributed control system, which leads to clock asynchrony among control system components and asynchrony-induced delays. This paper employs a flexible Time Division Multiple Access (F-TDMA) scheduler to manage the communication flows. And the stability of the close-loop system is guaranteed by using the pole placement method. The results of the simulation illustrate that the proposed method can effectively deal with the clock asynchrony problems and guarantee the stability of the system.